The relationship between religiosity and entrepreneurship interest. mediation roles of belief in upper power and fear of entrepreneurship - Indawati Nino; Septia Dioh; Jappy Fanggidae (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to investigate the mechanism of the relationship between the level of religiosity of youth and the interest in entrepreneurship in Kupang City. Students at one of the universities in Kupang City were chosen as respondents for this research because they are a demographic group that is hoped to be capable of creating employement by becoming entrepreneurs after graduating from college. To gain the intended research purposes, in the present paper we use literature from religiosity, entrepreneurship and psychology in order to build hypotheses. The data were analyzed with Structural Equation Modeling (SEM) techniques using SmartPLS software. The present study found that religiosity has a positive influence on interest in entrepreneurship as mediated by belief in upper power and fear of entrepreneurship. Theoretical and practical implications of the study are discussed.